2019
DOI: 10.1093/aje/kwz140
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Approach to Assessing Infectious Disease Risk: Identifying Risk Classes Based on Psychological Characteristics

Abstract: Prevention of infectious diseases depends on health-related behavior, which is often influenced by psychological characteristics. However, few studies assessing health-related behavior have examined psychological characteristics to identify risk groups, and this multidimensional approach might improve disease risk assessment. We aimed to characterize subgroups based on psychological characteristics and examine their influence on behavior and disease risk, using chlamydia as a case study. Selected participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, the sample size was large enough to conduct the LCA, and fit statistics of these analyses showed that the latent class model performed well. Furthermore, the behavioral and psychological measures included in the LCA have been identified as predictors for STI diagnosis in previous work in the same cohort, and, therefore, could be viewed as reliable proxy measures for STI risk 16,18 . Second, the majority of participants were highly educated Dutch females, which means that the results may not be generalizable to the general population 15,29 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Nevertheless, the sample size was large enough to conduct the LCA, and fit statistics of these analyses showed that the latent class model performed well. Furthermore, the behavioral and psychological measures included in the LCA have been identified as predictors for STI diagnosis in previous work in the same cohort, and, therefore, could be viewed as reliable proxy measures for STI risk 16,18 . Second, the majority of participants were highly educated Dutch females, which means that the results may not be generalizable to the general population 15,29 .…”
Section: Discussionmentioning
confidence: 98%
“…Impulsiveness has often been associated with high numbers of partners and higher STI risk. 16,18,27 Impulsive individuals may focus their attention more on immediate rewards of the situation, compared with more reflective individuals, which explains their propensity toward risky decision making. 28 Therefore, as the duration of strict COVID-19 restrictions was not known, impulsive individuals might have had more difficulty complying with physical distancing measures in terms of reducing (sexual) contacts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychological mechanisms of behaviour, such as risk perception, knowledge, or attitudes regarding condom use and STI testing [5][6][7][8] , may play an important role in improving STI control 9,10 . For example, psychological characteristics may also help to identify different types of individuals in a population at high risk for acquiring chlamydia (i.e., many partners and inconsistent condom use) that would not be identified based on sexual behaviour alone 11,12 . Previous studies showed that high impulsiveness [13][14][15] , low perceived importance of health 8 , and STI-related stigma and shame [16][17][18][19] , are associated with risky decisionmaking in terms of sexual behaviour.…”
mentioning
confidence: 99%